2005
DOI: 10.1007/s00239-004-0144-2
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of NIN-Like Proteins in Arabidopsis, Rice, and Lotus japonicus

Abstract: Genetic studies in Lotus japonicus and pea have identified Nin as a core symbiotic gene required for establishing symbiosis between legumes and nitrogen fixing bacteria collectively called Rhizobium. Sequencing of additional Lotus cDNAs combined with analysis of genome sequences from Arabidopsis and rice reveals that Nin homologues in all three species constitute small gene families. In total, the Arabidopsis and rice genomes encode nine and three NIN-like proteins (NLPs), respectively. We present here a bioin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
262
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(284 citation statements)
references
References 29 publications
14
262
0
8
Order By: Relevance
“…Previously, some studies have reported that several gene families could arise through tandem duplication of chromosomal regions, resulting in a clustered occurrence of family members, or through segmental duplication, resulting in a scattered occurrence of family members (Schauser et al, 2005). We assume that the expansion of the cucumber MLO gene family mainly resulted from segmental duplications rather than tandem duplication.…”
Section: Discussionmentioning
confidence: 83%
“…Previously, some studies have reported that several gene families could arise through tandem duplication of chromosomal regions, resulting in a clustered occurrence of family members, or through segmental duplication, resulting in a scattered occurrence of family members (Schauser et al, 2005). We assume that the expansion of the cucumber MLO gene family mainly resulted from segmental duplications rather than tandem duplication.…”
Section: Discussionmentioning
confidence: 83%
“…Sequence comparison between NIN and Mid revealed a conserved RWP-RK motif, which contains an invariant RWP3RK sequence (Schauser et al 1999). More NINlike proteins were lately identified in pea (Borisov et al 2003), rice, and Arabidopsis (Schauser et al 2005). In total, 14 proteins in Arabidopsis and 16 in rice contain this conserved motif.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that these diploids always mate as minus indicates that minus is dominant to plus (Harris 1989), a phenomenon found to be controlled by the MID gene (Galloway and Goodenough 1985). MID encodes a transcription factor in the RWP-RK family that also includes several proteins in higher plants that are suggested to exert their function during nitrogen limitation (Schauser et al 1999(Schauser et al , 2005Borisov et al 2003).Previous studies revealed that MID is necessary and sufficient to convert wild-type plus gametes to mate as minus: mt 1 cells transformed with the MID gene differentiate as minus gametes (Ferris and Goodenough 1997), and mt À cells carrying loss-of-function MID mutations (mid-1 or mid-2) differentiate as plus gametes (Ferris and Goodenough 1997;Ferris et al 2002). In fact, although the mid mutants express plus flagellar agglutinins (Ferris and Goodenough 1997;Ferris et al 2002) and plus mating structures (Ferris and Goodenough 1997), they are unable to fuse with minus gametes due to the lack of FUS1, a gene restricted to the MT 1 locus and encoding a glycoprotein required for fusion (Ferris et al 1996;Misamore et al 2003); hence the phenotype of mid mutants is designated pseudo-plus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, only a few transcription factors (ANR1, NLP7, LBD37/38/39, SPL9 (refs 6-9)) implicated in the regulation of gene expression by nitrate have been identified, and most of these factors are encoded by genes that are themselves regulated by nitrate at the transcriptional level. One exception is NIN-Like Protein7 (NLP7), a putative transcription factor that is expressed constitutively and shares homology with NIN (for Nodule INception), an essential protein for nodulation in legumes 10 . Molecular and physiological analyses suggest that NLP7 is involved in plant responses to nitrate 7 .…”
mentioning
confidence: 99%